A new flow pattern map for flow boiling in microfin tubes. (June 2015) - Rollmann, P.; Spindler, K.
Highlights: The flow patterns during flow boiling in a microfin tube were measured optically. The measurements based on the intensity of reflected laser light at phase interfaces. The transition curves for a new flow pattern map for microfin tubes are derived. Abstract: The flow patterns during flow boiling of R134a in a horizontal microfin tube have been measured optically in a contiguous glass tube. The microfin tube is made of copper with a total fin number of 60 and a helix angle of 18 ° . The fin height is 0.25 mm and the inner tube diameter at fin root is 8.72 mm. The copper tube is 0.5 m long. It is heated electrically. The glass tube is made of borosilicate glass. The inner tube diameter is 8.8 mm. The experiments have been conducted at the saturation temperature 10 ° C and the heat flux 10, 000 W m 2 . The mass flux has been varied between 15 and 300 kg s m 2 in steps of 5 and 10 kg s m 2, respectively. The vapor quality in the glass tube has been varied between 0.1 and 0.9 in steps of 0.1 . The optical measurements based on the different intensity of reflected laser light at the phase interfaces. No reflections have been detected at the glass–liquid interface while there have been reflections at the glass–vapor interface. The laser source has been rotated by 360 ° around the glass tube. Every 2.25 ° measurements of the intensity have been made. Because of the different wetting behavior flow pattern maps for smooth tubes are not suitable for determining the flow patterns in microfin tubes. Due to the helical structure of the fins there is a new flow pattern, the helix flow, where the liquid phase flows helically through the microfin tube. Because of the large wetted surface this leads to an increase of the heat transfer coefficient. The transition curves for a new flow pattern map for microfin tubes are being derived.